Influencer Credibility And Instagram Users' Purchase Interest - Prabowo, Ayudita Farrahsasti Kusuma Putri; Kriyantono, Rachmat; Kasim, Azahar (Universitas Brawijaya, 2024)
This research aims to determine the level of relationship between beauty influencer Tasya Farasya’s credibility, as well as its three indicators: trustworthiness, expertiseness, and attractiveness, with her follower’s purchase interest on the Instagram social media account @tasyafarasya for Somethinc’s skincare products. The population in this study is 6.3 million followers of the @tasyafarasya account, from which a sample of 135 respondents was then taken using slovin formula. The data in this research was obtained through a survey method by distributing questionnaires via Google Form, then the data was analyzed using the Pearson’s Correlation Product Moment test. The research results show that there is a significant and strong level of the correlation between Beauty Influencer Tasya Farasya’s credibility and her follower’s purchase interest on the Instagram account @tasyafarasya for Somethinc skincare products, which is proven by the Sig. value is 0,000 (p < 0,05) and the correlation coefficient is 0,73 (0,60 – 0,79: Strong correlation; high). This research contributes to proving that the use of influencers is a significant strategy in marketing products in digital media, as is true in conventional media